2005
DOI: 10.1590/s0100-204x2005000900010
|View full text |Cite
|
Sign up to set email alerts
|

Variabilidade genética e ecológica de Stylosanthes macrocephala determinadas por RAPD e SIG

Abstract: Resumo -Stylosanthes macrocephala M. B. Ferr. et S. Costa é uma leguminosa utilizada sob consorciação em pastagens, adubação e recuperação de áreas degradadas. A falta de características morfológicas e agronômicas estáveis e de informações ecogeográficas dos locais de coleta dos acessos tem dificultado o melhoramento genético da espécie. A fim de obter descritores ecológicos, moleculares e avaliar a variabilidade genética da coleção de S. macrocephala, 87 acessos foram analisados com o auxílio do Sistema de In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 12 publications
2
16
1
3
Order By: Relevance
“…However, studies with Stylosanthes in other regions of the country showed that the genetic variability between and within species of Stylosanthes is related to different regions of collection (BARROS et al, 2005;SANTANA et al, 2012), which was not observed in the present study. In other species of the genus Stylosanthes (S. capitata and S. guianenses), the presence of pollinating insects increased the crossing rates by 31% and 26%, respectively, as well as changed the fertilization rate in the progeny (SANTOS-GARCIA et al, 2011;, favouring the genetic variation in this material.…”
Section: Figurecontrasting
confidence: 76%
“…However, studies with Stylosanthes in other regions of the country showed that the genetic variability between and within species of Stylosanthes is related to different regions of collection (BARROS et al, 2005;SANTANA et al, 2012), which was not observed in the present study. In other species of the genus Stylosanthes (S. capitata and S. guianenses), the presence of pollinating insects increased the crossing rates by 31% and 26%, respectively, as well as changed the fertilization rate in the progeny (SANTOS-GARCIA et al, 2011;, favouring the genetic variation in this material.…”
Section: Figurecontrasting
confidence: 76%
“…Group I included the accessions BGFAB1, BGFAB2, BG-FAB4, BGFAB6, BGFAB9, and BGFAB7, collected in São João, PI, and accession BGFAB8, collected in Teresina, PI, suggesting that the last did not originate from the area in which it was collected. Groups II, III and IV comprised one accession each (BGFAB5, BGFAB10 and BGFAB3, respectively), indicating that the diversity of the species could be better exploited if more accessions were collected, confirming the conclusion of Barros et al (2005) based on the identification of groups of S. macrocephala containing few accessions. When individual accessions were pairwise compared, the highest genetic similarity coefficients were observed between group I accessions BGFAB7 from Teresina and BGFAB8 from São João and accessions BGFAB6 and BGFAB9 from São João, while the lowest coefficient was observed between accessions BGFAB10 (group III) and BGFAB3 (group IV).…”
Section: Resultssupporting
confidence: 54%
“…The coefficients of genetic similarity between accessions of P. moniliformis ranged from 0.11 to 0.56 (Table 2). This variation was greater than that observed with domesticated and autogamous forage legumes such as Stylosanthes macrocephala (Barros et al, 2005) and Vigna radiata (Lakhanpaul et al, 2000). Table 2.…”
Section: Resultsmentioning
confidence: 74%
“…DNA was amplified according to Barros et al (2005). To obtain the RAPD markers, 12 Operon ® primers were used: OPA (01, 04, 08, 09, 18, and 20), OPM (03), OPS (07), OPV (05 and 12), OPAB (09), and OPAF (05).…”
Section: Molecular Analysis With Rapd Markersmentioning
confidence: 99%